Landscape drivers of mammal habitat use and richness in a protected area and its surrounding agricultural lands - Bellón, Beatriz; A.W. Henry, Dominic; Renaud, Pierre-Cyril; Roque, Fabio de O.; Santos, Cyntia Cavalcante; Melo, Isabel; Arvor, Damien; de Vos, Alta (Agriculture, ecosystems & environment, 2022)
Protected areas (PAs) are key to conserving biodiversity and ecosystem services globally, but their effectiveness increasingly depends on the ability of the surrounding agricultural areas to support biodiversity and secure connectivity at the landscape level. This requires monitoring the broader multi-use landscapes in which PAs exist and identifying the landscape characteristics that support rich, functional wildlife communities. Here, we investigated the species richness and habitat use patterns of a mammal community in relation to different landscape variables and land use and land cover (LULC) types in a PA and its surrounding agricultural lands in the Cerrado. We first used a hierarchical multi-species occupancy model with input camera trap data and eight landscape variables (vegetation productivity, phenology, and heterogeneity, distance to water, roads and settlements, and the PA, slope, and elevation) to estimate the species richness and habitat use of 29 mammal species across the landscape. We then analyzed the relationships between the species richness and habitat use and the landscape variables at the site level, as well as the distribution of species at the landscape level in relation to the different natural and agricultural LULC types. We found that most species are present in the native forest areas across the landscape and that many species are also present in the croplands surrounding the PA. The results also showed that species’ habitat use was especially determined by the productivity and heterogeneity of the vegetation cover, with a particularly strong positive relation in grasslands and pastures. These results suggest that the private properties surrounding the PA might be playing an essential role in supporting biodiversity in this region and provide insights on management practices that could largely contribute to maintaining or promoting a multifunctional landscape, such as maintaining the remaining forests or increasing the productivity and the heterogeneity (e.g., by increasing tree cover) in pastures. •Mammal species richness was highest in forests and croplands.•Productive and heterogeneous vegetation hosted a higher number of species.•Many threatened species were present in open areas, including croplands.•NDVI-based variables were key predictors of mammal habitat use.•Conservation planning around protected areas is important to support biodiversity.